DEVELOPMENT OF MAGAZINE AS A LEARNING MEDIA ON ENDOCRINE SYSTEM - Putri Anggraini; Ruqiah Ganda Putri Panjaitan; Eko Sri Wahyuni (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2021)
The magazine is one of the learning media that is rarely used in school. This research aimed to know the feasibility of endocrine system magazines and examine the learners' response to magazines as the media. This type of research is research and development. Five expert judgments tested the feasibility of the magazine. The aspects that were assessed were the material and media aspects. The product trials were done on nine students—the responses measured included cognitive, affective, and conative. The result of this research showed, on the feasible test CVR score of the material and media aspects was 1. Moreover, the CVI score was one as well. On the product trial, the score for cognitive aspect 85,18%, affective 83,33%, conative 87,77%, and the average responses 85,42%. It can be concluded that endocrine system magazine was feasible as learning media. Furthermore, magazines as a media gained a positive and strong response. So magazines can be a choice of media that can help learning activities.